Evolution of the Conceptualization of Filial Piety in the Global Context: From Skin to Skeleton - Bedford, Olwen; Yeh, Kuang-Hui (Frontiers in Psychology, 2021)
Social science researchers often define filial piety as a set of norms, values, and practices regarding how children should behave toward their parents. In this article, we trace the conceptual development of filial piety research in Chinese and other societies to highlight the assumptions underlying this traditional approach to filial piety research. We identify the limitations of these assumptions, including the problem of an evolving definition and lack of cross-cultural applicability. We then advocate an alternative framework that overcomes these limitations by focusing on the deep structure of filial piety: the dual filial piety model (DFPM). The DFPM applies the concept of contextualized personality to reconceptualize filial piety in terms of authoritarian and reciprocal psychological motivations particular to the parent-child context. Because the focus is on a universal psychological mechanism rather than cultural norms, values, and behavior, the DFPM may be applied for investigation of filial piety at individual, social, and cultural levels within and across various societies. We discuss application of the DFPM in relation to existing filial piety and intergenerational relations research from several societies and conclude with a comparison to other recent proposals for measuring Chinese filial piety.